Fruit rot disease in butternut squash caused by Pythium aphanidermatum in Trincomalee district, Sri Lanka - Sevvel, P.; Kugathasan, D.; Jeyaseelan, E.C. (University of Jaffna, 2020)
Fruit rot disease is a serious, emerging problem in butternut squash (Cucurbita moschata) cultivation in Northern and Eastern Provinces of Sri Lanka. Aim of the present study was to identify the causative agent of the fruit rot in the Trincomalee District and find a suitable fungicide to control the disease. Diseased fruit samples were collected randomly from four fields in Nilaveli, Morawewa, Kinniya and Thambalagamam. Fruit rots appeared brown colour, sunken and water-soaked spots which later turned black, enlarged rots with moldy appearance. The pathogen was isolated on Potato Dextrose Agar (PDA) medium. Cultural and morphological characteristics were studied. On PDA, cultures initially appeared white, cottony with heavy aerial mycelium which later became flat. Younger hyphae had swollen tips, while matured hyphae were hyaline, aseptate and dichotomously branched. Aplerotic oospores were surrounded by terminal oogonia. Zoospores arose from globose sporangia. There was no morphological variation among isolates, collected from the four different villages in the Trincomalee district. Internal transcribed spacer (ITS) region of the genome was PCR amplified. PCR products were subjected to DNA sequencing. Based on morphological features and analysis of ITS region of the genome, the pathogen was identified as Pythium aphanidermatum. Koch’s postulates confirmed the pathogenicity of P. aphanidermatum. Four concentrations (10, 100, 1,000 and 10,000 ppm) of commercial fungicides (Captan 50 WP, Mancozeb 80 WP, Homai 80 WP and Topsin 70 WP) were tested against the isolate in vitro. Fungicides, namely Homai or Captan (>1000 mg l-1), can be used to reduce the pathogen growth.
Keywords: Fruit rot; Butternut squash; Pythium aphanidermatum